2020
DOI: 10.1038/s41598-020-64288-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profile analysis of two Vicia faba cultivars with contrasting salinity tolerance during seed germination

Abstract: Faba bean (Vicia faba L.) is an important food legume crop. Salinity soils severely constrain the production of faba bean, however, the seed germination of faba bean, which is a vital plant growth stage, is sensitive to salinity. Planting improved varieties of faba bean, which exhibit salt tolerance in seed germination stage, is an optimal strategy for faba bean product. To investigate the genes dynamics during the seed germination stage under salinity, RNA-seq method was used to investigate genome-wide transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…Notwithstanding, Chang et al [95] reported that salinity interferes with the ethylene signaling pathway and decreases ethylene production in seeds of C. sativus, which was associated with the inhibition of germination. In Faba beans (Vicia faba), seed germination in salinity-tolerant Y134 is not inhibited during salinity stress as compared to the salinity-sensitive Y078 probably because of the downregulation of genes related to ABA and ethylene signaling pathways and upregulation of late embryogenesis abundant (LEA) genes [106]. Seeds of Capsicum annuum primed with SA showed higher a germination rate due to suppression of the ethylene level as well as elevation of total soluble sugar contents and SOD activity [107].…”
Section: Seed Germination Regulated By Ethylene Under Salinity Stressmentioning
confidence: 99%
“…Notwithstanding, Chang et al [95] reported that salinity interferes with the ethylene signaling pathway and decreases ethylene production in seeds of C. sativus, which was associated with the inhibition of germination. In Faba beans (Vicia faba), seed germination in salinity-tolerant Y134 is not inhibited during salinity stress as compared to the salinity-sensitive Y078 probably because of the downregulation of genes related to ABA and ethylene signaling pathways and upregulation of late embryogenesis abundant (LEA) genes [106]. Seeds of Capsicum annuum primed with SA showed higher a germination rate due to suppression of the ethylene level as well as elevation of total soluble sugar contents and SOD activity [107].…”
Section: Seed Germination Regulated By Ethylene Under Salinity Stressmentioning
confidence: 99%
“…Salinity can affect seed germination by creating the osmotic potential to prevent water uptake and/or by providing conditions for the entry of ions that may be toxic to the embryo or developing seedling. At the seed germination stage, salt stress restricts water absorption, inhibits the growth of the embryo axis and leads to secondary seed dormancy [ 41 ]. Brachypodium had a decreased germination efficiency under saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous RNA-seq study detected six DEGs between two asparagus bean (Vigna unguiculata) cultivars with contrasting salt-induced phenotypes that were grown under saline and control conditions [55]. In another study, two faba bean varieties with contrasting salt tolerance during the germination stage underwent salt and control treatments to investigate the genome-wide transcription profiles via RNA-seq [56]. Moreover, 13 genes responsive to salinity during the germination stage were revealed by a genome-wide association analysis and the RNA sequencing of 196 upland cotton genotypes [57].…”
Section: Discussionmentioning
confidence: 99%